Zellweger Syndrome: A Downs Syndrome Mimic - Dr. Tanmay Khadpe; Dr. Alpana Kondekar; Dr. Varun Anand; Dr. Radha Ghildiyal (Pediatric Review: International Journal of Pediatric Research, 2019)
The peroxisomal diseases are genetically determined disorders caused either by the failure to form or maintain the peroxisome or by a defect in the function of a single protein that is normally located in this organelle. It is a heterogeneous group of autosomal recessive disorders characterized by a defect in peroxisome formation and are caused by mutations in one of 13 PEX genes. The defect in peroxisome formation or impaired metabolic pathways result in metabolic abnormalities. Typically in Zellweger spectrum disorders (ZSD) patients accumulate very long chain fatty acids (VLCFAs), phytanic and pristanic acid, C27-bile acid intermediates and pipecolic acid in plasma and have a deficiency of plasmalogens in erythrocytes.These disorders present with a wider range of phenotype than has been recognized in the past and few of them may phenotypically resemble Downs Syndrome.